Mathematical Modeling for Evaluating the Hydraulic and Thermodynamic Performance of the Hamada–Zawiya Pipeline: A Novel Net Exergy Improvement through Heating (NEIH) Index and Enhanced Light-Crude-Oil Transport Efficiency (مجلة الفاروق للعلوم, 2026)
Long-distance crude-oil transportation through pipelines is subject to significant operational and hydraulic challenges arising from thermal variations, which directly affect the fluid’s rheological and physical properties. This study develops an integrated mathematical modeling framework to evaluate the influence of temperature on the rheological, hydraulic, and thermodynamic behavior of Hamada light crude oil (42.6° API) flowing through the 387-km Hamada–Zawiya pipeline. The Andrade model was employed to represent the temperature dependence of dynamic viscosity, while the Swamee–Jain equation was used to calculate the friction factor under turbulent-flow conditions. The analysis further introduces the Net Exergy Improvement through Heating (NEIH) index, which quantitatively balances the mechanical-exergy savings obtained from reducing viscous losses against the thermal exergy consumed in heating the crude oil.Simulation results showed that increasing the operating temperature sharply reduced the dynamic viscosity from 11.84 cP at 10°C to 1.85 cP at 100°C, accompanied by an increase in the Reynolds number (Re) from 42,422 to 250,373. The total pressure drop decreased from 137.02 bar to 91.41 bar as flow resistance declined, thereby generating substantial mechanical-energy savings. The NEIH index also demonstrated a clear advantage over the conventional index: it increased from a negative value of −5.3437 at 10°C to a maximum of 6.4777 at 20°C, revealing an improved balance between thermal and mechanical exergy and enabling the identification of the most energy-efficient thermal operating range. The proposed model provides a quantitative framework for evaluating crude-oil pipeline performance and supporting decisions aimed at optimizing energy consumption and thermodynamic efficiency.